Prescriptions and perceptions on the role of non-academic personnel in Quezon City a comparative study - Elican, Amparo E. 1940- (s.n.], 1969)
The study compared prescriptions and perceptions of the role of non-academic personnel in Quezon City using checklists and interviews. The study provides empirical indices as to the directions presently given by incumbent administrators to this part of the labor force, and it poses implications for pre-service and in-service training programs for administrators in their job positions.